Tradução, adaptação transcultural e validação do Banco de Itens Saúde Global do Patient-Reported Outcomes Measurement Information System - PROMIS® - para a Língua Portuguesa - Zumpano, Camila Eugênia (2015)
The use of Patient-Reported Outcomes Measures (PROMs), which considers the patient\'s perspective on his/her own health and treatment, has gained importance on clinical practice and research. The Patient-Reported Outcomes Measurement Information System (PROMIS®) revolutionized the area when it started providing precise and valid item banks in different health domains, calibrated by the Item Response Theory (IRT), and used for the evaluation of the impact of different chronic diseases on the patient\'s quality of life. The aim of this study was to translate, cross-culturally adapt and validate the PROMIS® Global Health Item Bank into Portuguese. The Functional Assessment of Chronic Illness Therapy (FACIT) methodology was used to translate and cross-culturally adapt the ten items of the bank. The final version of the assessment tool translated into Portuguese was self-administered in 1010 patients. The statistical analysis conducted were: ceiling and floor effects, internal consistency reliability, test-retest reliability, convergent validity, construct validity through exploratory and confirmatory factor analysis, and item calibration through Samejima\'s Graded Response Model (GRM). Four global items needed to be adjusted after pre-test. The analysis of the psychometric properties showed that the PROMIS® Global Health Item Bank has good reliability Cronbach\'s alpha was 0.83 and intra-class correlation coefficient was 0.89. The correlation between the assessment tool and the physical and psychological domains of the WHOQOL-bref ranged from moderated to strong (rho = 0.478 and 0.571, respectively). The exploratory and confirmatory factor analysis confirmed the validity of the item bank, since they showed a good adjustment to the two dimensional model previously established (Global Physical Health scale: CFI = 0.99, TLI = 0.98, RMSEA = 0.04, SRMR = 0.019; Global Mental Health scale: CFI = 1.00, TLI = 1.00, RMSEA = 0.00, SRMR = 0.011). The Global Physical Health and Global Mental Health scales showed good coverage of the latent trait according to Samejima s Graded Response Model. The PROMIS® Global Health Item Banks translated into Portuguese achieved conceptual, semantic, cultural, and operational equivalences, and demonstrated satisfactory psychometric properties regarding its use in Brazilian patients for clinical practice and research.